Steel plate and method for producing the same
By adjusting the addition ratio of Ti and N and the casting cooling speed, TiN is not decomposed during large-line energy welding, the problem of reducing HAZ toughness is solved, and the low-temperature toughness of HAZ is improved, which is suitable for welding of large structures.
Patent Information
- Application Number
- CN202180065720.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-11-05
- Filing Date
- 2021-10-29
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2041-10-29
Smart Images

Figure BDA0004143811940000191 
Figure BDA0004143811940000201 
Figure BDA0004143811940000211
Abstract
Description
Technical Field
[0001] The present invention relates to a steel plate, and more particularly to a steel plate applicable to high-heat input welding and a method for manufacturing the same. Specifically, the present invention relates to a steel plate having excellent toughness in the HAZ after high-heat input welding. In addition, the steel plate of the present invention can be well used in large structures such as ships, marine structures, cryogenic storage tanks, buildings and civil engineering structures. Background Art
[0002] In recent years, structures such as ships, marine structures, cryogenic storage tanks, buildings, and civil engineering structures have been growing in size, and the steel used has been actively promoted to be stronger and thicker.
[0003] In order to efficiently manufacture the above-mentioned structures in a short time, it is desirable to adopt high-heat input welding methods represented by submerged arc welding, gas-electrode welding, electroslag welding, etc. However, when high-heat input welding is performed on steel plates, there is the following problem: a large amount of heat is transferred to the heat affected zone (HAZ) of the steel plate, thereby damaging the characteristics of the HAZ.
[0004] For example, during high heat input welding, the HAZ is exposed to a high temperature just below the melting point, and the austenite grains tend to coarsen. The coarse austenite grains transform into an upper bainite structure containing island-shaped martensite with poor toughness due to subsequent cooling. Therefore, the toughness of the HAZ tends to decrease.
[0005] Many countermeasures have been proposed so far to address the problem of reduced toughness of the HAZ caused by high heat input welding.
[0006] For example, Patent Document 1 describes a technique for finely dispersing TiN in steel to suppress the coarsening of austenite grains. Patent Document 2 describes a technique for dispersing stable Ti oxides at a higher temperature.
[0007] Furthermore, from the viewpoint of reducing island martensite (MA) in the HAZ, Patent Document 3 discloses a technique for reducing the content of P in addition to reducing the contents of C and Si.
[0008] Prior art literature
[0009] Patent Literature
[0010] Patent Document 1: Japanese Patent Publication No. 55-026164
[0011] Patent Document 2: Japanese Patent Application Laid-Open No. 57-051243
[0012] Patent Document 3: Japanese Patent Application Publication No. 2008-163446 Summary of the invention
[0013] However, the above-mentioned technology of using TiN to refine austenite has the following problems: when high-input energy welding is performed, the heat-affected zone is heated to the melting temperature range of TiN, thereby TiN decomposes and the above-mentioned dispersion effect disappears, or due to the solid solution Ti and solid solution N generated by the decomposition of TiN, the matrix structure of the steel becomes brittle, thereby significantly reducing the toughness of the heat-affected zone.
[0014] In addition, the above-mentioned technology of refining austenite using Ti oxides has a problem that it is difficult to disperse predetermined oxides finely and uniformly in the steel sheet.
[0015] Furthermore, the above-mentioned technique of reducing the P content for the purpose of reducing the MA content causes a deviation in the suppression of the MA content due to the distribution of P which is likely to segregate at grain boundaries, etc., and is insufficient from the viewpoint of uniformly reducing the MA content in the HAZ structure.
[0016] Therefore, in view of the above-mentioned actual situation, an object of the present invention is to provide a steel plate having excellent low-temperature toughness of a HAZ formed during high-heat input welding (hereinafter referred to as high-heat input HAZ) and a method for producing the steel plate.
[0017] In order to solve the above-mentioned problems, the inventors have conducted intensive studies on a method for improving the low-temperature toughness of a high-heat-input HAZ, and as a result, obtained the following findings.
[0018] First, the inventors believed that the effect of TiN in suppressing the coarsening of austenite grains could be maintained by dispersing TiN finely and in large quantities and suppressing the decomposition of TiN during high heat input welding.
[0019] Therefore, the inventors conducted intensive studies and found that by adjusting the addition amounts of Ti and N so that the mass % ratio of Ti to N, i.e., Ti / N, is within the range of 2.10 to 3.60 and the component composition satisfies the following formula (1), and by setting the average cooling rate when casting molten steel to obtain a steel billet, especially the average cooling rate at a position 1 mm from the steel billet surface, to 100° C. / min or more, TiN can be finely and abundantly dispersed, and the decomposition of TiN can be suppressed during high-heat-input welding.
[0020] 169≤5158×Ti+25563×N≤309· · · (1).
[0021] In addition, it was found that by containing C, Si, Mn, Al, Nb, Ti, and N in a specified range and controlling the carbon equivalent Ceq within a specified range, the formation of island martensite (MA) in the HAZ can be effectively suppressed, so that the low-temperature toughness of the high-heat input HAZ can be obtained that is better than before.
[0022] The present invention has been completed through further studies based on the above findings.
[0023] That is, the gist of the present invention is as follows.
[0024] 1. A steel sheet having the following composition: containing, by mass%, C: 0.045% to 0.080%, Si: 0.02% or more and less than 0.10%, Mn: 1.60% or more and less than 1.95%, P: 0.010% or less, S: 0.010% or less, Al: 0.010% to 0.100%, Nb: 0.005% to 0.050%, O: 0.0100% or less, Cu: 0.50% or less, Ni: 0. 50% or less, Cr: 0.50% or less, Mo: 0.30% or less, V: 0.30% or less, Ti: 0.010% to 0.025% and N: 0.0038% to 0.0084%, with respect to Ti and N, the mass % ratio of Ti to N, i.e., Ti / N, being 2.10 to 3.60 and satisfying the following formula (1), and the carbon equivalent Ceq represented by the following formula (2) being 0.400 to 0.500, and the remainder being Fe and unavoidable impurities;
[0025] The average particle size of TiN particles present at a depth of 1 mm from the steel sheet surface is 20 nm to 50 nm, and the density is 5.0×10 8 Pieces / cm 2 above;
[0026] 169≤5158×Ti+25563×N≤309··· (1)
[0027] Ceq=C+Mn / 6+(Cu+Ni) / 15+(V+Mo+Cr) / 5··· (2)
[0028] Here, each element symbol represents the content (mass %) of each component, and is 0 when not contained.
[0029] 2. The steel sheet according to 1, further comprising, in mass %, one or more selected from the group consisting of W: 0.30% or less, Co: 0.30% or less, B: 0.0100% or less, Ca: 0.0100% or less, Mg: 0.0100% or less, and REM: 0.0200% or less.
[0030] 3. The steel sheet according to 2, wherein the B content is B: 0.0002% to 0.0012%.
[0031] 4. A method for manufacturing a steel plate, characterized in that molten steel having the following composition is cast to obtain a steel billet, and then the steel billet is hot rolled, wherein the average cooling rate during the casting is 100°C / min to 500°C / min;
[0032] The composition includes, by mass%, C: 0.045% to 0.080%, Si: 0.02% or more and less than 0.10%, Mn: 1.60% or more and less than 1.95%, P: 0.010% or less, S: 0.010% or less, Al: 0.010% to 0.100%, Nb: 0.005% to 0.050%, O: 0.0100% or less, Cu: 0.50% or less, Ni: 0.50% or less. , Cr: 0.50% or less, Mo: 0.30% or less, V: 0.30% or less, Ti: 0.010% to 0.025% and N: 0.0038% to 0.0084%, with respect to Ti and N, the mass % ratio of Ti to N, i.e., Ti / N, being 2.10 to 3.60 and satisfying the following formula (1), and the carbon equivalent Ceq represented by the following formula (2) being 0.400 to 0.500, and the remainder being Fe and unavoidable impurities;
[0033] 169≤5158×Ti+25563×N≤309··· (1)
[0034] Ceq=C+Mn / 6+(Cu+Ni) / 15+(V+Mo+Cr) / 5··· (2)
[0035] Here, each element symbol represents the content (mass %) of each component, and is 0 when not contained.
[0036] 5. According to the method for manufacturing a steel plate described in 4, the molten steel further contains, in terms of mass %, one or more selected from the group consisting of W: 0.30% or less, Co: 0.30% or less, B: 0.0100% or less, Ca: 0.0100% or less, Mg: 0.0100% or less, and REM: 0.0200% or less.
[0037] 6. The method for manufacturing a steel plate according to 5, wherein the content of the B in the molten steel is B: 0.0002% to 0.0012%.
[0038] According to the present invention, a steel plate having excellent toughness even in a high-input heat input welded joint and a method for manufacturing the steel plate can be provided.
[0039] The steel plate obtained in the present invention is suitable for high-heat-input welding with excellent workability during construction of container ships, for example, and therefore has a significant effect industrially. DETAILED DESCRIPTION
[0040] Next, embodiments of the present invention will be described in detail.
[0041] <Steel Plate>
[0042] The steel sheet of the present invention has a specified composition. The content of each element of C, Si, Mn, P, S, Al, Nb, O, Cu, Ni, Cr, Mo, V, Ti and N is specified in the composition of the steel sheet of the present invention. At the same time, for Ti and N, the range of the mass % ratio of Ti to N (Ti / N) and the formula (1) are also specified, and the range of Ceq shown in the formula (2) is further specified.
[0043] Since the steel plate of the present invention can exhibit excellent toughness in a large-heat input welded joint, it can be applied to large structures such as container ships.
[0044] In addition, the steel sheet of the present invention can be obtained by, for example, the production method described below.
[0045] [Ingredients]
[0046] First, the reasons for limiting the chemical composition of the steel sheet of the present invention will be described.
[0047] In addition, below, "%" about the chemical composition of a steel plate means "mass %" unless otherwise specified.
[0048] (C: 0.045%~0.080%)
[0049] C is an element that improves the grain boundary strength and contributes to the toughness of the HAZ. It is an element required to achieve the desired HAZ toughness value. In addition, it is also an element required to achieve the strength of the substrate. In order to obtain these effects, the C content is set to 0.045% or more. In addition, from the viewpoint of improving the grain boundary strength and improving the HAZ toughness value, the C content is preferably 0.050% or more, and more preferably 0.055% or more. On the other hand, if the C content is too much, the toughness of the HAZ decreases. In particular, for the HAZ, if the C content is too much, high-heat input welding causes austenite coarsening phase transformation and the formation of MA, thereby greatly reducing the toughness of the HAZ. From the viewpoint of preventing these, the C content is set to 0.080% or less. In addition, from the viewpoint of further suppressing the reduction in the toughness of the HAZ, the C content is preferably 0.075% or less.
[0050] (Si: 0.02% or more and less than 0.10%)
[0051] Si is an element that has the function of inhibiting the formation of coarse carbides and improving the toughness of the HAZ. It is an element required to achieve the desired HAZ toughness value. In addition, it is also a component required to ensure substrate strength and deoxidation. In order to obtain these effects, the Si content is set to 0.02% or more. In addition, from the viewpoint of improving the HAZ toughness value, the Si content is preferably 0.03% or more, and more preferably 0.04% or more. On the other hand, if the Si content is too much, the formation of MA is caused by high-input energy welding, thereby greatly reducing the toughness of the HAZ. Therefore, in order to ensure high HAZ weldability, the Si content is set to less than 0.10%. From the viewpoint of further optimizing the toughness of the HAZ, the Si content is preferably 0.09% or less, and more preferably 0.08% or less.
[0052] (Mn: 1.60% or more and less than 1.95%)
[0053] Mn is an element that increases the hardenability of steel, suppresses the formation of coarse carbides, ensures the strength of the substrate and improves the toughness of the HAZ. It is an element required to achieve the desired HAZ toughness value. In order to obtain these effects, the Mn content is set to 1.60% or more. In addition, from the viewpoint of improving the toughness value of the HAZ, the Mn content is preferably 1.65% or more, and more preferably 1.70% or more. On the other hand, if the Mn content is too much, in addition to reducing the toughness of the HAZ, the alloy cost will become too high. From these viewpoints, the Mn content is set to less than 1.95%. In addition, from the viewpoint of further suppressing the reduction of the toughness of the HAZ and further controlling the cost, the Mn content is preferably 1.90% or less, and more preferably 1.85% or less.
[0054] (P: 0.010% or less)
[0055] P has the adverse effect of reducing HAZ toughness through grain boundary segregation. Therefore, it is preferred to reduce the P content as much as possible, but if it is below 0.010%, it is allowed. On the other hand, the lower limit of the P content is not particularly limited and can be 0%. Generally, P is an element contained as an inevitable impurity in steel, so it can also be greater than 0% in industry. In addition, if P is reduced excessively, it will lead to an increase in refining costs, so from the perspective of cost, the P content is preferably above 0.005%.
[0056] (S: 0.010% or less)
[0057] S exists in steel as sulfide inclusions such as MnS, which has the adverse effect of reducing the toughness of the HAZ and becoming the starting point of brittle fracture. Therefore, it is preferred to reduce the S content as much as possible, but if it is less than 0.010%, it is allowed. On the other hand, the lower limit of the S content is not particularly limited and can also be 0%. Generally, S is an element contained as an inevitable impurity in steel, so it can also be greater than 0% in industry. In addition, if S is reduced excessively, it will lead to an increase in refining costs, so from a cost point of view, the S content is preferably 0.005% or more.
[0058] (Al: 0.010% to 0.100%)
[0059] Al acts as a deoxidizer, so it is an element that has the effect of reducing oxide inclusions and improving HAZ toughness. In addition, it has the effect of improving the strength of the substrate. In order to obtain these effects, the Al content is set to 0.010% or more. On the other hand, if the Al content is greater than 0.100%, the oxide inclusions increase, the cleanliness decreases, and the HAZ toughness decreases. Therefore, the Al content is set to 0.100% or less. It should be noted that the Al content is preferably 0.050% or less, and more preferably 0.040% or less.
[0060] (Nb: 0.005% to 0.050%)
[0061] Nb is an element that has the effect of improving the toughness of HAZ by refining the grain size. In addition, it also has the effect of improving the strength and toughness of the substrate. In order to obtain the above-mentioned effect, the Nb content is set to 0.005% or more. It should be noted that the Nb content is preferably 0.007% or more, and more preferably 0.009% or more. On the other hand, if the Nb content is greater than 0.050%, MA is formed in the HAZ and the toughness is reduced. Therefore, the upper limit of the Nb content is set to 0.050%. From the viewpoint of improving the toughness of the HAZ, the Nb content is preferably 0.045% or less, more preferably 0.040% or less, and further preferably 0.035% or less.
[0062] (O: 0.0100% or less)
[0063] O is an element contained as an inevitable impurity, but in the present invention, since it is an element that needs to be particularly reduced, the content is specified. O forms oxides that become the starting point of brittle fracture, and has the adverse effect of reducing the toughness of the HAZ. Therefore, the O content is limited to less than 0.0100%. The O content is preferably less than 0.0050%, and more preferably less than 0.0030%. On the other hand, the lower limit of the O content is not particularly limited and can also be 0%. Generally, since O is an element contained as an inevitable impurity in steel, it can be greater than 0% industrially. In addition, if O is reduced excessively, the refining cost will increase. From the perspective of cost, the O content is preferably more than 0.0020%.
[0064] (Cu: 0.50% or less)
[0065] Cu is an element that increases the hardenability of steel and improves the strength of the steel plate (substrate), and can be added arbitrarily. When Cu is added, in order to obtain the above-mentioned effect, the content of Cu added is preferably 0.01% or more. On the other hand, if the Cu content is greater than 0.50%, the toughness of the HAZ deteriorates and the alloy cost increases. Therefore, when Cu is added, the Cu content is set to 0.50% or less. It should be noted that the Cu content is more preferably 0.20% or more. On the other hand, the Cu content is more preferably 0.40% or less, and further preferably 0.30% or less.
[0066] (Ni: 0.50% or less)
[0067] Ni, like Cu, is an element that has the effect of improving the strength of the steel plate (substrate) and can be added arbitrarily. When Ni is added, in order to obtain the above-mentioned effect, the content of added Ni is preferably 0.01% or more. On the other hand, if the Ni content is greater than 0.50%, the weldability will deteriorate and the alloy cost will increase. Therefore, when Ni is added, the Ni content is set to 0.50% or less. It should be noted that the Ni content is more preferably 0.20% or more. On the other hand, the Ni content is more preferably 0.40% or less, and further preferably 0.30% or less.
[0068] (Cr: 0.50% or less)
[0069] Cr, like Cu, is an element that has the effect of improving the strength of the steel plate (base material) and can be added arbitrarily. In order to obtain the above-mentioned effect, the content of added Cr is preferably 0.01% or more. On the other hand, if the Cr content is greater than 0.50%, the weldability will deteriorate and the alloy cost will increase. Therefore, when Cr is added, the Cr content is set to 0.50% or less. It should be noted that the Cr content is more preferably 0.05% or more. On the other hand, the Cr content is more preferably 0.40% or less, and more preferably 0.30% or less.
[0070] (Mo: 0.30% or less)
[0071] Mo is an element that has the effect of improving the strength of the steel plate (base material) like Cu, and can be added arbitrarily. In order to obtain the above-mentioned effect, the Mo content is preferably 0.01% or more. On the other hand, if the Mo content is greater than 0.30%, the weldability will deteriorate and the alloy cost will increase. Therefore, when Mo is added, the Mo content is set to 0.30% or less. It should be noted that the Mo content is more preferably 0.05% or more. On the other hand, the Mo content is more preferably 0.20% or less.
[0072] (V: 0.30% or less)
[0073] V is an element that has the effect of improving the strength of the steel plate (base material) like Cu, and can be added arbitrarily. In order to obtain the above-mentioned effect, the V content is preferably 0.01% or more. On the other hand, if the V content is greater than 0.30%, the weldability will deteriorate and the alloy cost will increase. Therefore, when V is added, the V content is set to 0.30% or less. It should be noted that the V content is more preferably 0.05% or more. On the other hand, the V content is more preferably 0.20% or less.
[0074] (Ti: 0.010% to 0.025%)
[0075] Ti is an element that forms TiN and precipitates when the steel solidifies, which helps to suppress the coarsening of austenite grains in the weld heat affected zone and becomes a ferrite phase transformation nucleus to help increase toughness. It is also one of the important elements in the present invention. From the perspective of the toughness of the HAZ, in order to ensure the necessary amount, it is preferred to contain 0.010% TiN. It should be noted that the Ti content is more preferably 0.012% or more, and further preferably 0.014% or more. On the other hand, if more than 0.025% is added, the problem of large-scale generation of TiN or coarsening of TiN grains makes it impossible to obtain the expected effect. As a result, the toughness of the weld zone is reduced. Therefore, the upper limit of the Ti content is preferably 0.025%. In addition, from the perspective of improving toughness, it is more preferably 0.023% or less, more preferably 0.021% or less, and further preferably 0.019% or less.
[0076] (N: 0.0038% or more and 0.0084% or less)
[0077] N is an element required to form the above-mentioned TiN. In order to ensure the necessary amount from the viewpoint of the toughness of the HAZ, it is preferred to contain 0.0038% or more of TiN. It should be noted that the N content is more preferably 0.0040% or more, and further preferably 0.0042% or more. On the other hand, if more than 0.0084% is added, a large amount of TiN is formed, thereby reducing the toughness of the weld zone. Therefore, the upper limit of the N content is preferably 0.0084%. In addition, from the viewpoint of improving toughness, the N content is more preferably 0.0082% or less, further preferably 0.0080% or less, and further preferably 0.0078% or less.
[0078] Ti and N are elements that precipitate as TiN during steel solidification, contribute to suppressing the coarsening of austenite grains in the weld heat affected zone, and contribute to high toughness by becoming ferrite transformation nuclei. They play an important role in the present invention, and are contained in the following ranges.
[0079] (Ti / N: 2.10~3.60)
[0080] When the mass % ratio of Ti to N (Ti / N) is less than 2.10, the amount of solid-solution N that does not form TiN increases, which reduces the toughness of the HAZ. Therefore, Ti / N is set to be greater than 2.10. It should be noted that Ti / N is preferably greater than 2.20, and more preferably greater than 2.30. On the other hand, if Ti / N is greater than 3.60, TiN coarsens, reducing the toughness of the weld zone. Therefore, the upper limit of Ti / N is set to 3.60. In addition, from the viewpoint of improving the toughness of the HAZ, it is preferably less than 3.50, and more preferably less than 3.40. In addition, the content (mass %) of each element in Ti / N is in steel.
[0081] (169≤5158×Ti+25563×N≤309···(1))
[0082] In the past, the technology of using TiN to improve the toughness of the HAZ during high-input energy welding had the following problems: TiN decomposed due to the exposure of the heat affected zone to high-input energy welding, thereby eliminating its dispersion effect, or the solid solution Ti and solid solution N generated by the decomposition embrittled the matrix structure of the steel, thereby significantly reducing the toughness of the HAZ.
[0083] In the present invention, in order to suppress the decomposition of TiN, it is crucial to set the value of 5158×Ti+25563×N (also referred to as the value of formula (1) in the present invention) to be greater than 169. From the viewpoint of further improving the HAZ toughness, the value of formula (1) is preferably greater than 169, more preferably greater than 175, and even more preferably greater than 180.
[0084] On the other hand, if the value of the above formula (1) is greater than 309, a large amount of TiN is generated, resulting in a decrease in the toughness of the HAZ. Therefore, the value of the above formula (1) is set to 309 or less. From the viewpoint of further improving the toughness, the value of the formula (1) is preferably less than 309, more preferably 280 or less, and further preferably 260 or less.
[0085] (Carbon equivalent Ceq: 0.400~0.500)
[0086] In order to achieve excellent strength of the steel sheet (substrate), it is important to set the carbon equivalent Ceq defined by the following formula (2) to 0.400 or more. In order to obtain the above effect, Ceq is preferably 0.410 or more, more preferably 0.420 or more, and further preferably 0.430 or more.
[0087] Ceq=C+Mn / 6+(Cu+Ni) / 15+(V+Cr+Mo) / 5··· (2)
[0088] On the other hand, if Ceq is greater than 0.500, MA is formed in the high heat input HAZ, and the toughness of the HAZ decreases. Therefore, Ceq is set to 0.500 or less. It should be noted that from the perspective of component cost, Ceq is preferably 0.490 or less, and more preferably 0.480 or less.
[0089] The basic component composition of the steel sheet of the present invention includes the above-described elements in the content, and the remainder is Fe and other inevitable impurities. For the purpose of further improving the characteristics, especially the strength or the base toughness and the HAZ toughness, the basic component composition may further contain one or more selected from W: 0.30% or less, Co: 0.30% or less, B: 0.0100% or less, Ca: 0.0100% or less, Mg: 0.0100% or less, and REM: 0.0200% or less.
[0090] (W: 0.30% or less)
[0091] W is an element that has the effect of improving the strength of the steel plate (base material) like Cu, and can be added arbitrarily. In order to obtain the above-mentioned effect, the W content is preferably 0.01% or more. On the other hand, if the W content is greater than 0.30%, the weldability will deteriorate and the alloy cost will increase. Therefore, when W is added, the W content is set to 0.30% or less. It should be noted that the W content is more preferably 0.05% or more. On the other hand, the W content is more preferably 0.20% or less.
[0092] (Co: 0.30% or less)
[0093] Co, like Cu, is an element that has the effect of improving the strength of the steel plate (base material) and can be added arbitrarily. In order to obtain the above-mentioned effect, the Co content is preferably 0.01% or more. On the other hand, if the Co content is greater than 0.30%, the weldability will deteriorate and the alloy cost will increase. Therefore, when Co is added, the Co content is set to 0.30% or less. It should be noted that the Co content is more preferably 0.05% or more. On the other hand, the Co content is more preferably 0.20% or less.
[0094] (B: 0.0100% or less)
[0095] B is an element that has the effect of significantly improving hardenability even when added in trace amounts. Therefore, the strength of the steel plate (substrate) can be improved. In addition, it helps to improve the hardenability of the HAZ, thereby inhibiting the formation and growth of coarse ferrite structure, and by forming precipitates with N, it helps to refine the structure as a phase transformation nucleus, so it can also improve the toughness of the HAZ. In order to obtain the above-mentioned effect, when B is added, the B content is preferably 0.0001% or more. On the other hand, if the B content is greater than 0.0100%, coarse Fe-B carbides may be formed. The coarse Fe-B carbides serve as the starting point of fracture and significantly reduce the toughness of the substrate and HAZ. Therefore, when B is added, the B content is set to 0.0100% or less. It should be noted that the B content is more preferably 0.0050% or less, more preferably 0.0030% or less, more preferably 0.0012% or less, and further preferably 0.0010% or less. Furthermore, when B is added, the upper limit of the B content is preferably set as described above also from the viewpoint of avoiding high alloying and controlling costs.
[0096] (Ca: 0.0100% or less)
[0097] Ca is an element that combines with S to suppress the formation of MnS and the like that elongates in the rolling direction. Therefore, by adding Ca, the morphology can be controlled so that the sulfide inclusions are spherical, and the toughness of welded joints and the like can be improved. In order to obtain this effect, when Ca is added, the Ca content is preferably 0.0005% or more, and more preferably 0.0020% or more. On the other hand, if the Ca content is greater than 0.0100%, the cleanliness of the steel decreases. The decrease in cleanliness leads to a decrease in the toughness of the HAZ. Therefore, when Ca is added, the Ca content is set to 0.0100% or less. It should be noted that the Ca content is more preferably 0.0050% or less, and further preferably 0.0025% or less.
[0098] (Mg: 0.0100% or less)
[0099] Like Ca, Mg is also an element that has the effect of inhibiting the formation of MnS and the like that elongates in the rolling direction by combining with S. Therefore, by adding Mg, the morphology can be controlled so that the sulfide inclusions are spherical, and the toughness of welded joints and the like can be improved. In order to obtain the above-mentioned effects, when Mg is added, the Mg content is preferably 0.0005% or more, and more preferably 0.0020% or more. On the other hand, if the Mg content is greater than 0.0100%, the cleanliness of the steel decreases. The decrease in cleanliness leads to a decrease in the toughness of the HAZ. Therefore, when Mg is added, the Mg content is set to 0.0100% or less. It should be noted that the Mg content is more preferably 0.0050% or less, and further preferably 0.0025% or less.
[0100] (REM: 0.0200% or less)
[0101] Like Ca and Mg, REM (rare earth metal) is also an element that has the effect of inhibiting the formation of MnS and the like that elongates along the rolling direction by combining with S. Therefore, by adding REM, the morphology can be controlled so that the sulfide inclusions are spherical, and the toughness of welded joints and the like can be improved. In order to obtain the above-mentioned effects, when REM is added, the REM content is preferably 0.0005% or more, and more preferably 0.0015% or more. On the other hand, if the REM content is greater than 0.0200%, the cleanliness of the steel decreases. The decrease in cleanliness leads to a decrease in the toughness of the HAZ. Therefore, when REM is added, the REM content is set to 0.0200% or less. It should be noted that the REM content is more preferably 0.0100% or less, further preferably 0.0080% or less, and further preferably 0.0050% or less.
[0102] [TiN particle size and density]
[0103] Next, TiN in the steel sheet of the present invention, particularly TiN particles located at a depth of 1 mm from the surface of the steel sheet, will be described.
[0104] The average particle size of TiN particles at a depth of 1 mm from the steel plate surface: 20 nm to 50 nm
[0105] TiN is a precipitate that precipitates during steel solidification and helps to suppress the coarsening of austenite grains in the heat affected zone of welding or becomes a ferrite phase transformation nucleus to help increase toughness. It plays an important role in the present invention. When the average particle size of TiN particles is less than 20nm, TiN decomposes during welding and its dispersion effect disappears. The solid solution Ti and solid solution N generated by the decomposition will make the matrix structure of the steel embrittled, and the toughness of the HAZ is significantly reduced. Therefore, the average particle size of the TiN particles at a depth of 1mm from the surface of the steel plate is set to be greater than 20nm. It should be noted that from the perspective of effectively improving the toughness of the HAZ, the above-mentioned average particle size is preferably greater than 25nm, and more preferably greater than 30nm. In addition, if the average particle size is greater than 50nm, the inhibitory effect of the coarsening of austenite grains is reduced, and the toughness of the HAZ is reduced. Therefore, the average particle size of TiN at a depth of 1mm from the surface is set to be less than 50nm. From the perspective of improving the toughness of the HAZ, the above-mentioned average particle size is preferably less than 45nm, and more preferably 40nm.
[0106] The density of TiN particles at a depth of 1 mm from the steel plate surface is 5.0×10 8 Pieces / cm 2 above
[0107] In order to achieve the effect of suppressing the coarsening of austenite grains in the heat affected zone of welding and increasing toughness by forming ferrite transformation nuclei, it is important to disperse TiN particles in large quantities. 2 Dispersion 5.0×10 8 Therefore, the density of TiN particles at a depth of 1 mm from the steel sheet surface is set to 5.0×10 8 Pieces / cm 2 It should be noted that from the viewpoint of effectively improving the HAZ toughness, the density is preferably 8.0×10 8 Pieces / cm 2 , and more preferably 1.0×10 9 Pieces / cm 2 above.
[0108] On the other hand, the upper limit of the density is not particularly limited, but from the content of Ti and N specified in the present invention, if the density is too high, the average particle size of TiN will be too fine, so it is actually 1.0×10 10 Pieces / cm 2 the following.
[0109] It should be noted that the TiN particles in the present invention refer to precipitates containing 10% or more of Ti and N, respectively. In addition, the average particle size and density of the TiN particles are obtained by taking a sample from a position 1 mm deep from the surface of the steel plate as an observation surface, and determining the area circle equivalent diameter and the number of TiN particles in an arbitrary range of 10 μm×10 μm observed by a microscope, and can be calculated from them.
[0110] The characteristics of the joint produced by high-input heat welding are mainly achieved by designing the composition of the steel billet within the above-mentioned steel plate composition range and the manufacturing method of the steel billet, and are not affected by hot rolling during steel plate manufacturing or the characteristics after hot rolling. It should be noted that, for example, the plate thickness, strength, toughness, and microstructure of the steel plate (base material) suitable for the side panel of the hatch of a container ship are as follows.
[0111] [Plate thickness]
[0112] The thickness of the steel plate of the present invention is not particularly limited. For example, when applied to the hatch side coaming of a container ship, a steel plate of 50 mm or more is actually suitable, and a steel plate of 75 mm or more is more preferred.
[0113] [Base material strength]
[0114] The strength of the steel plate (base material) of the present invention is not particularly limited. For example, when applied to the hatch side panels of container ships, it is recommended that the yield strength at the half thickness position (also referred to as 1 / 2t) be 390 MPa or more, preferably 430 MPa, and more preferably 460 MPa or more.
[0115] [Base material toughness]
[0116] The toughness of the steel plate of the present invention is not particularly limited. For example, when applied to the hatch side panels of container ships, it is recommended that the toughness at the quarter thickness position be 53 J or more, preferably 64 J or more, and more preferably 75 J or more.
[0117] In order to obtain the above-mentioned plate thickness and substrate strength, the ideal microstructure of the steel plate of the present invention is described below. In the composition of the present invention, the pearlite fraction in the ferrite-pearlite structure is reduced. Therefore, it is difficult to ensure the specified substrate strength. Therefore, the volume fraction of bainite at the 1 / 2t position at the center of the plate thickness is preferably 80% or more, more preferably 90% or more, and can also be 100%. By setting the volume fraction of bainite to the above-mentioned range, the specified substrate strength and substrate toughness can be ensured.
[0118] In addition, as long as the volume fraction of bainite satisfies the above range, structures other than bainite such as ferrite and pearlite, which are generally considered to be the structure of a steel sheet, may exist in the remaining microstructures.
[0119] <Method for manufacturing steel sheet>
[0120] The particle size and density of TiN particles that affect the joint characteristics are affected by the composition of the steel billet and the casting process. Therefore, in the method for manufacturing the steel plate of the present invention, in addition to the composition of the steel mentioned above, only the conditions of the casting process for obtaining the steel billet for hot rolling are specified. The manufacturing methods and conditions other than these are not particularly limited, and the heating process can be performed after the casting process and before the hot rolling process. In addition, the cooling process can also be performed after the hot rolling process. And, for example, when applied to the hatch side panel of a container ship, it is preferred that the heating temperature of the heating process; the rolling start temperature of the hot rolling process, the cumulative reduction rate of the non-recrystallized area and the rolling end temperature; the cooling start temperature, the average cooling rate and the cooling stop temperature of the cooling process are adjusted according to the following conditions.
[0121] The steel plate obtained by the manufacturing method satisfying these conditions has excellent base material strength and excellent toughness in the high heat input HAZ, and can be suitably used in the manufacture of large structures such as container ships.
[0122] The manufacturing conditions of the steel billet are not particularly limited except for the cooling rate when obtaining the steel billet such as the slab. The steel billet is produced by, for example, using a known melting method such as a converter to produce molten steel having the above-mentioned composition, preferably using a known casting method such as a continuous casting method to obtain a steel billet such as a slab having a desired size.
[0123] [Casting process]
[0124] Molten steel having the above-mentioned composition can be used for casting. In addition, the above-mentioned molten steel used for casting can reach 1400°C or above.
[0125] (Average cooling rate: 100℃ / min~500℃ / min)
[0126] When obtaining a steel billet by casting, the key lies in the cooling conditions during casting. That is, when casting a steel billet, within the temperature range of 1400-1250°C where TiN precipitates at a position 1 mm from the surface of the steel billet, if the average cooling rate is less than 100°C / min, the size of TiN in the base material (steel plate) in the finished steel plate will coarsen. If the size of TiN coarsens, the TiN density of the base material (steel plate) will decrease, and the austenite structure in the high-heat HAZ will coarsen, which may reduce the toughness of the HAZ.
[0127] Therefore, in the method for manufacturing the steel plate of the present invention, the average cooling rate during casting (the average cooling rate of the steel billet) is set to be above 100°C / min. The above average cooling rate is preferably above 150°C / min, and more preferably above 200°C / min. On the other hand, if the cooling rate of the steel billet is greater than 500°C / min, the density of TiN increases, the size of TiN is refined, TiN is dissolved during high-heat welding, and the austenite grains are coarsened, so the toughness of the HAZ deteriorates. In addition, since cracks are generated on the surface of the steel billet, costs are required to remove the cracks, and the yield of the material may be reduced. Therefore, the average cooling rate during casting is set to be below 500°C / min. The above average cooling rate is preferably below 400°C / min, and more preferably below 300°C / min.
[0128] In addition, the temperature range for measuring the above average cooling rate is 1400 to 1250°C.
[0129] Unless otherwise specified, the temperature in each step described below is the temperature at the center of the plate thickness (1 / 2t) of each steel material.
[0130] [Heating process]
[0131] (Heating temperature: 950℃~1250℃)
[0132] The heating temperature of the steel billet in the heating process is preferably 950°C to 1250°C. When the heating temperature is less than 950°C, the heating temperature is too low, the deformation resistance increases, and the load on the hot rolling mill increases, so it may be difficult to carry out subsequent hot rolling. On the other hand, when the heating temperature is a high temperature greater than 1250°C, the austenite grains coarsen, which not only leads to a decrease in the toughness of the steel plate substrate and the high-heat HAZ, but also significant oxidation, increased oxidation loss, and a possible decrease in the yield. It should be noted that the heating temperature is more preferably above 1000°C. On the other hand, the heating temperature is more preferably below 1150°C.
[0133] [Hot rolling process]
[0134] (Rolling start temperature: Ar3 point + 100°C or above)
[0135] When the steel billet heated as described above is hot rolled, when the rolling start temperature is less than Ar3 point + 100°C, the austenite grains are not refined due to insufficient recrystallization in the hot rolled plate being hot rolled. In this way, if a hot rolled plate in which the austenite grains are not sufficiently refined is used to manufacture a steel plate, the toughness of the steel plate may be reduced. Therefore, the rolling start temperature is preferably Ar3 point + 100°C or more. From the viewpoint of ensuring the rolling time in the non-recrystallized region described later, the rolling start temperature is more preferably Ar3 point + 150°C or more, and further preferably Ar3 point + 200°C or more. It should be noted that the upper limit of the rolling start temperature is not particularly limited, and is about the heating temperature of the above-mentioned steel billet.
[0136] It should be noted that the Ar3 point (°C) can be obtained according to the following formula (3).
[0137] Ar3 point (℃) = 910-273C-74Mn-57Ni-16Cr-9Mo-5Cu···(3)
[0138] Here, the symbol of each element in the formula (3) represents the content (mass %) of the element in the steel, and an element not contained is represented by 0.
[0139] (Cumulative reduction rate in non-recrystallized region: 40% or more)
[0140] In the non-recrystallized region (in the present invention, the region where the temperature of the steel billet is less than Ar3 point + 100°C), if the cumulative reduction rate is less than 40%, sufficient processing effect cannot be obtained for austenite, which may lead to a decrease in the toughness of the base material in the finished steel plate. Therefore, the cumulative reduction rate in the non-recrystallized region is preferably 40% or more. From the viewpoint of further improving the toughness of the base material, it is preferably 45% or more, and more preferably 50% or more.
[0141] (Rolling end temperature: Ar3 point or above)
[0142] The hot rolling process is preferably completed at a temperature above the Ar3 transformation point (°C). If the temperature during hot rolling is lower than the Ar3 transformation point (°C), a large amount of ferrite is formed in the steel, so the volume fraction of bainite cannot be increased, and the specified strength may not be obtained. In addition, the lower the temperature, the higher the deformation resistance, and the greater the load on the hot rolling mill. It should be noted that from the perspective of ensuring the subsequent cooling start temperature, the hot rolling temperature is preferably above the Ar3 point + 20°C.
[0143] [Cooling process]
[0144] (Cooling start temperature: Ar3 point or above)
[0145] The hot rolled sheet obtained by the hot rolling is preferably cooled at a temperature above the Ar3 transformation point (°C). When the cooling start temperature is lower than the Ar3 transformation point (°C), a large amount of ferrite is formed in the steel, so the volume fraction of bainite cannot be increased, and the specified strength may not be obtained. Therefore, the cooling start temperature is preferably above the Ar3 point (°C).
[0146] (Average cooling rate at 600-500°C: 2.0°C / s or more)
[0147] If the average cooling rate after the above-mentioned start of cooling is less than 2.0°C / s, it becomes slow cooling, and a large amount of ferrite is formed in the steel. Therefore, the volume fraction of bainite cannot be increased, and the substrate may not reach the specified strength. Therefore, the average cooling rate to below 500°C in the cooling process is preferably above 2.0°C / s. On the other hand, the upper limit of the average cooling rate is not particularly limited, but the maximum industrial cooling rate at the 1 / 2 position of the plate thickness of a 50mm plate is 20°C / s. In order to avoid the increase in cooling costs caused by excessive cooling, it is preferably below 20°C / s. It should be noted that the temperature range for measuring the above-mentioned average cooling rate is in the range of 600 to 500°C.
[0148] (Cooling stop temperature: 500°C or less)
[0149] The cooling process for performing the above cooling is preferably performed at a 1 / 2t temperature of 500°C or less, that is, preferably at a cooling stop temperature of 500°C or less. If the cooling stop temperature is higher than 500°C, a large amount of ferrite is generated in the steel, so the volume fraction of bainite cannot be increased, and the substrate may not reach the specified strength. On the other hand, there is no lower limit for the cooling stop temperature, but if the cooling stop temperature is too low, the shape of the steel plate deteriorates, so it is preferably about 200°C, and more preferably about 300°C.
[0150] By subjecting the steel billet having the above-mentioned composition to the above-mentioned manufacturing process, a base material (steel plate) having the microstructure of the present invention can be obtained. Thus, the high-heat input HAZ of the obtained steel plate has excellent toughness and is a preferred steel plate suitable for the hatch side coaming part of a container ship.
[0151] Here, in the present invention, regarding the substrate properties described in detail in the examples, the yield strength (YS): 390 MPa or more is set as an excellent strength property, and the absorbed energy at -40°C (vE-40°C): 53 J or more is set as an excellent substrate toughness. In addition, for the toughness of the HAZ, the absorbed energy at -20°C (vE-20°C): 46 J or more is set as excellent toughness. In addition, for the toughness of the HAZ, the case of vE-20°C of 53 J or more is set as more excellent toughness, the case of 64 J or more is set as further excellent toughness, and the case of 92 J or more is set as particularly excellent toughness.
[0152] The steel plate of the present invention can effectively prevent the coarsening of austenite grains in a high heat input HAZ, and can obtain a high vE-20° C. in a welded joint including the HAZ. Therefore, the steel plate of the present invention is suitable for high heat input welding.
[0153] Example
[0154] Below, based on embodiment, the present invention is specifically described.It should be noted that the following embodiment is a preferred example representing the present invention, and the present invention is not limited in any way.In addition, the following embodiment can also be changed to implement in the scope that meets the gist of the present invention, and such a mode is also included in the technical scope of the present invention.
[0155] Molten steel having the composition shown in Table 1 was prepared and cast into steel billets (slabs) under the conditions shown in Table 2. Under the conditions shown in Table 2, the steel billets were sequentially subjected to a heating process, a hot rolling process and a cooling process to obtain individual steel plates.
[0156] The average particle size and density of TiN particles at a depth of 1 mm from the surface and the volume fraction of bainite at a depth of 1 / 2 plate thickness from the surface (in this embodiment, the center of the plate thickness is also recorded as 1 / 2t) were measured for each steel plate obtained. In addition, the yield strength (YS) and base toughness (vE-40°C) were evaluated as steel plate substrate properties.
[0157] In addition, a V-notch process was performed on the test plate for the joint obtained from the above steel plate, and a high-heat input welding with a welding input of 200 kJ / cm was performed using a commercially available low-temperature steel welding wire to produce a high-heat input welded joint. The toughness of the HAZ was then evaluated using the obtained joint. Each test method was performed as follows. It should be noted that the characteristics evaluated using the joint obtained in this way are referred to as joint characteristics.
[0158] [Average particle size and density of TiN particles at a depth of 1 mm from the surface]
[0159] The sample was obtained from the steel plate at a depth of 1 mm from the surface of the steel plate as the observation surface. A thin film sample was prepared from the obtained sample by the extraction replication method, and an image of 10 μm×10 μm was taken using a transmission electron microscope (TEM). Furthermore, by EDX analysis, for Ti and N precipitates containing more than 10% each, the area circle equivalent diameter and number of precipitates were analyzed from the taken images using an image analyzer, thereby calculating the average particle size and density.
[0160] [Microstructure at 1 / 2t]
[0161] (Volume fraction of bainite)
[0162] The sample was obtained from the steel plate at a depth of 1 mm from the surface of the steel plate as the observation surface. After the surface of the obtained sample was mirror-polished and further etched with nitric acid, an image of 10 mm × 10 mm was taken using a scanning electron microscope (SEM). The image was analyzed using an image analyzer to determine the fraction of bainite structure, and this value was used as the volume fraction of bainite.
[0163] In either case, when the fraction of microstructures is determined, the identification of bainite structure is performed as follows. That is, a SEM image is obtained by taking a picture at a magnification of 500 to 3000 times. In the SEM image, a ferrite structure having a thin and long-growing lamellar shape and containing a carbide structure having a circle equivalent diameter of 0.05 μm or more is identified as a bainite structure.
[0164] [Substrate properties]
[0165] (Base material strength)
[0166] A No. 14A test piece of JIS Z 2201 is obtained from the center of the thickness of the steel plate in a direction perpendicular to the rolling direction, with the center of the plate thickness (the position of 1 / 2 of the plate thickness) being the center of the test piece. The obtained test piece is subjected to a tensile test according to the main requirements of JIS Z 2241, and the yield strength YS (unit: MPa) measured is used as the base material strength.
[0167] (Base material toughness)
[0168] The NK U4 impact test piece was obtained from the 1 / 4 thickness position of the steel plate in the direction parallel to the rolling direction, and the 1 / 4 thickness position of the plate was made the center and the notch position of the test piece. The obtained test piece was subjected to a Charpy impact test at a test temperature of -40°C, and the average value of the absorbed energy vE-40°C (unit: J) of the three test pieces subjected to the same conditions was taken as the substrate toughness.
[0169] [HAZ characteristics]
[0170] (HAZ toughness)
[0171] The NK U4 impact test piece was obtained with a depth of 1mm from the surface of the joint obtained by high-input energy welding as the test piece surface layer, and the HAZ was set as the notch position. The obtained test piece was subjected to a Charpy impact test at a test temperature of -20°C, and the average value of the absorbed energy vE-20°C (unit: J) of the three test pieces tested under the same conditions was taken as the toughness of the HAZ.
[0172] The evaluation results obtained in this way are recorded in Table 2.
[0173]
[0174]
[0175]
[0176]
[0177] As shown in Table 2, the high heat input HAZ vE-20°C of any of the inventive examples of the present invention reached 46 J or more. In addition, the steel plates manufactured within the preferred range all showed high strength of the base material YS of 390 MPa or more and base material toughness of 53 J or more, and had both base material strength and base material toughness. It can be seen that the steel plates of the inventive examples have excellent high heat input weldability.
[0178] On the other hand, since the steel plates Nos. 18 to 40 and 56 to 64 corresponding to comparative examples all have steel billet material compositions that do not satisfy the conditions of the present invention, it is found that the HAZ toughness is low or the HAZ toughness and the base material YS are low.
[0179] In addition, although the component compositions of the steel plates No. 5 and 6 corresponding to the comparative examples satisfy the conditions of the present invention, the average cooling rate during casting does not satisfy the conditions of the present invention. As a result, it can be seen that at least one of the average particle size and density of the TiN particles at a depth of 1 mm in the steel plates is outside the range of the present invention, and the toughness of the HAZ is low.
[0180] As described above, according to the present invention, it is possible to provide a steel plate having excellent joint toughness after high heat input welding.
Claims
1. A steel plate having the following composition: In terms of mass%, C: 0.045% to 0.080%, Si: 0.02% to less than 0.10%, Mn: 1.60% to less than 1.95%, P: 0.010% or less, S: 0.010% or less, Al: 0.010% to 0.100%, Nb: 0.005% to 0.050%, O: 0.0100% or less, Cu: 0.50% or less, Ni: 0.50% or less, Cr : 0.50% or less, Mo: 0.30% or less, V: 0.30% or less, Ti: 0.010% to 0.025% and N: 0.0038% to 0.0084%, with respect to Ti and N, the mass % ratio of Ti to N, i.e., Ti / N, being 2.10 to 3.60 and satisfying the following formula (1), the carbon equivalent Ceq represented by the following formula (2) being 0.400 to 0.500, and the remainder being Fe and unavoidable impurities; The average particle size of TiN particles present at a depth of 1 mm from the steel sheet surface is 20 nm to 50 nm, and the density is 5.0×10 8 pcs / cm 2 above, The volume fraction of bainite at the center of the plate thickness is more than 80%; 169≤5158×Ti+25563×N≤309・・・(1) Ceq=C+Mn / 6+(Cu+Ni) / 15+(V+Mo+Cr) / 5・・・(2) Here, each element symbol represents the content of each component in mass %, and is 0 when not contained.
2. The steel sheet according to claim 1, wherein the chemical composition is further selected from one or more of W: 0.30% or less, Co: 0.30% or less, B: 0.0100% or less, Ca: 0.0100% or less, Mg: 0.0100% or less, and REM: 0.0200% or less in terms of mass %.
3. The steel plate according to claim 2, wherein: The content of B is B: 0.0002% to 0.0012%.
4. A method for manufacturing a steel plate, characterized in that: The method for manufacturing a steel plate according to any one of claims 1 to 3 comprises casting molten steel having the following composition to obtain a steel billet, and then hot rolling the steel billet, wherein the average cooling rate during the casting is 100°C / min to 500°C / min; The composition is calculated by mass % as follows: C: 0.045% to 0.080%, Si: 0.02% or more and less than 0.10%, Mn: 1.60% or more and less than 1.95%, P: 0.010% or less, S: 0.010% or less, Al: 0.010% to 0.100%, Nb: 0.005% to 0.050%, O: 0.0100% or less, Cu: 0.50% or less, Ni: 0.50% or less , Cr: 0.50% or less, Mo: 0.30% or less, V: 0.30% or less, Ti: 0.010% to 0.025% and N: 0.0038% to 0.0084%, with respect to Ti and N, the mass % ratio of Ti to N, i.e., Ti / N, being 2.10 to 3.60 and satisfying the following formula (1), the carbon equivalent Ceq represented by the following formula (2) being 0.400 to 0.500, and the remainder being Fe and unavoidable impurities; 169≤5158×Ti+25563×N≤309・・・(1) Ceq=C+Mn / 6+(Cu+Ni) / 15+(V+Mo+Cr) / 5・・・(2) Here, each element symbol represents the content of each component in mass %, and is 0 when not contained.
5. The method for manufacturing a steel plate according to claim 4, wherein the component composition of the molten steel is further selected, in terms of mass %, from one or more of W: 0.30% or less, Co: 0.30% or less, B: 0.0100% or less, Ca: 0.0100% or less, Mg: 0.0100% or less, and REM: 0.0200% or less.
6. The method for manufacturing a steel plate according to claim 5, wherein: The content of B in the molten steel is B: 0.0002% to 0.0012%.
Citation Information
Patent Citations
JP1980026164B2
Steel products for welding
JP1982051243A
Steel member for high heat input welding
JP2008163446A
Heavy plate excellent in haz toughness
CN101285159A